A Canadian-wide perspective on the essential conditions for taking a comprehensive school health approach - Kacey C. Neely; Genevieve R. Montemurro; Kate E. Storey (BMC, 2020)
Abstract Background The primary purpose of this research was to explore Comprehensive School Health (CSH) stakeholders' perceptions of the essential conditions for taking a CSH approach in other contexts across Canada. The secondary purpose was to examine the need for and development of an evaluative tool or resource to assess the implementation of the essential conditions. Methods Data were generated through individual semi-structured interviews (n = 38) and small group interviews (n = 3) with 45 participants across Canada involved in implementing policies or programs which take a CSH approach. Interviews were subjected to content analysis. Results There was positive support for the essential conditions and results indicated the essential conditions are relevant across Canada. Findings revealed the necessity for a new essential condition that reflected support and leadership from the school district and/or provincial/territorial governing bodies. Modifications to the description of each of the essential conditions were also suggested to provide clarity. Results also indicated that an evaluative tool that was concise, meaningful, and provided immediate feedback would be useful to school communities to establish readiness, assess, and improve ongoing implementation of CSH approaches. Conclusions This research contributes to the evidence-base of CSH by providing school communities across Canada with a set of refined and understandable essential conditions that support successful implementation. Further, the development of an evaluation tool will support school health champions, researchers, and policymakers in the optimization and implementation of policies or programs which take a CSH approach, ultimately supporting healthier school communities across the country.